Altered Cellular Immunity and Differentially Expressed Immune-Related Genes in Patients With Systemic Sclerosis–Associated Pulmonary Arterial Hypertension - Tu, Jianxin; Jin, Jinji; Chen, Xiaowei; Sun, Li; Cai, Zhen (Frontiers in Immunology, 2022)
Systemic sclerosis (SSc) is the most common connective tissue disease causing the PAH.However, the cause and potential immune molecular events that associated with PAH are still unclear. Therefore, it is particularly essential to analyze the changes of SSc-PAH related immune cells and its immune-related genes. Three Microarray datasets (GSE22356, GSE33463, GSE19617) were obtained by GEO. Compared with SSc, we found the Neutrophils statistically more, while, T cells CD4 naive, T cells CD4 memory resting statistically less in PBMCs. Moreover, the results of GSEA showed there is a differential enrichment of multiple pathways between SSc and SSc-PAH. Via combined DEGs and IRGs, fifteen IRGs were selected. In addition, we also analyzed the first five rich KEGG pathways and the most abundant GO-molecular functional term. Furthermore, IL-7R, LCK, HDAC1 and EGFR genes were identified as hub genes via PPI network analysis. The Comparative Toxic Genomics Database (CTD) analyze result showed that LCK, HDAC1 and EGFR have a higher score with SSc. Co-expression network analysis confirmed that IL-7R, LCK, and HDAC1 are key genes related to immune regulation in SSc without PAH, and are involved in T cell immune regulation. Subsequently, using GSE22356&GSE33463 as the test set and GSE19617 as the verification set, it was verified that the mRNA expression levels of the three central genes of SSc-PAH were significantly lower than that of the SSc without PAH samples. Consistent with previous predictions, IL-7R, LCK, HDAC1 are positively correlated with T cell CD4 naiveness and T cell CD4 memory resting, while IL-7R, LCK and Neutrophils are negatively correlated. Therefore, these evidences may suggest that these 3 immune related genes: IL-7R, LCK, and HDAC1 may be highly related to the immunological changes in SSc-PAH and can reduce T cell in SSc-PAH PBMCs through the regulation of T cell activation,which suggest that these three molecules may be involved in the development of SSc-PAH.Finally, 49 target miRNAs of 3 specifically expressed hub genes were obtained, and 49 mRNA-miRNA pairs were identified, which provided directions for our further research.